2015
DOI: 10.14453/aabfj.v9i2.3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Government in MSMEs:The Empowerment of MSMEs During the Free Trade Era in Indonesia

Abstract: As the era of globalisation has progressed, the free-trade paradigm -in which the role of government in every aspect of economic development is minimised, replaced by the power of the free market -has inevitably spread across countries throughout the world. Despite the positive outcomes that can be obtained from the idea of free liberalisation in achieving economic growth and opportunities, this paper will propose that governments must continue to have a strong role in their countries' economies, particularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 4 publications
0
22
0
2
Order By: Relevance
“…The role of the Regional Government, that strategy of empowerment and the development of MSMEs, (Habiburahman, Alam, and Dunan, 2019). MSMEs benefit from the program in terms of improved productivity, marketing and insights into MSMEs as an economic sector, (Kusumawardhani, Rahayu, Maksum, 2015). Government policies have effect on the performance of MSMEs, (Andreastika, Santoso, Deoranto, 2017).…”
Section: The Role Of Government and A Competitiveness Of Msmesmentioning
confidence: 99%
“…The role of the Regional Government, that strategy of empowerment and the development of MSMEs, (Habiburahman, Alam, and Dunan, 2019). MSMEs benefit from the program in terms of improved productivity, marketing and insights into MSMEs as an economic sector, (Kusumawardhani, Rahayu, Maksum, 2015). Government policies have effect on the performance of MSMEs, (Andreastika, Santoso, Deoranto, 2017).…”
Section: The Role Of Government and A Competitiveness Of Msmesmentioning
confidence: 99%
“…We give her higher priority than the common people do. When harvest, The success may be in the form of increased productivity, efficiency, and marketing ( [6], p.22). Results of this research supported the findings of previous research conducted by Syamsulbahri and Brojonegoro (2006) that the highest percentage of success was found in East Java.…”
Section: Strategy Of Implementation Of a Technology Diffusion Policy mentioning
confidence: 99%
“…To elevate the quality of KUR program, government can include technological aspects in KUR distribution. A research by Kusumawardhani, Rahayu, and Maksum (2015) found that soft loans (in example KUR) to support technology, marketing, and other improvements in business capacity have proven successful in creating science-based MSMEs, increasing productivity and improving human-resources management and marketing. The solution of supporting the competitiveness of MSMEs through technology will work only if the government does think globally and act locally.…”
Section: Trend Of Effectivity Of Kur Distribution In Maluku Utara Promentioning
confidence: 99%